Mechanism exploration of the foamed asphalt binder using the Molecular Dynamics (MD) method. (10th November 2022) - Yao, Hui; Liu, Junfu; Wang, Yiran; li, Xin; Zeng, Jiani; Li, Jianrong; Ji, Jie; Dai, Qingli; You, Zhanping
Abstract: Due to the consideration of energy conservation and emission reduction, Warm Mix Asphalt (WMA) is used in construction and foamed asphalt is a common agent in WMA. The objective of this paper is to explore the foaming mechanism and distribution law of asphalt and its components, as well as its basic properties. The expansion rate and half-life were used to describe the foaming properties of the foamed asphalt and to determine the optimum water content. The microscopic images were aided to study morphological changes in the foamed asphalt. Moreover, Molecular Dynamics (MD) simulations were widely used in the study of asphalt materials such as self-healing, interfacial behaviors, and mechanical properties. Based on intermolecular interactions, energies, and trajectories, the mechanism and performance of foamed asphalt can also be investigated. The molecular model of the foamed asphalt was established, and the foaming process of the foamed asphalt was discussed based on the perspectives of the energy, density, and intermolecular agglomerations. The simulation results can be a valuable reference for industry and fundamental research.